The Effects and Meanings of Receiving a Diagnosis of Mild Cognitive Impairment or Alzheimer’s Disease When One Lives Alone - Portacolone, Elena (J Alzheimers Dis, 2018)
BACKGROUND: One third of older adults with cognitive impairment live alone and are at high risk for poor health outcomes. Little is known about how older adults who live alone experience the process of receiving a diagnosis of mild cognitive impairment (MCI) or Alzheimer’s disease (AD). OBJECTIVE: The aim of this study was to understand the effects and meanings of receiving a diagnosis of MCI or AD on the lived experience of older adults living alone. METHODS: This is a qualitative study of adults age 65 and over living alone with cognitive impairment. Participants’ lived experiences were elicited through ethnographic interviews and participant observation in their homes. Using a qualitative content analysis approach, interview transcripts and fieldnotes were analyzed to identify codes and themes. RESULTS: Twenty-nine older adults and 6 members of their social circles completed 114 ethnographic interviews. Core themes included: relief, distress, ambiguous recollections, and not knowing what to do. Participants sometimes felt uplifted and relieved by the diagnostic process. Some participants did not mention having received a diagnosis or had only partial recollections about it. Participants reported that, as time passed, they did not know what to do with regard to the treatment of their condition. Sometimes they also did not know how to prepare for a likely worsening of their condition, which they would experience while living alone. CONCLUSION: Findings suggest the need for more tailored care and follow-up as soon as MCI or AD is diagnosed in persons living alone.